Deterring Kickbacks and Encouraging Entry in Public Procurement Markets: Evidence from Firm Surveys in 90 Developing Countries. (14th February 2019) - Knack, Stephen; Biletska, Nataliya; Kacker, Kanishka
Abstract: There is little systematic evidence on the links between procurement systems and outcomes such as competition and corruption levels. This paper adds to the evidence, using data on 34, 000 firms from the World Bank's Enterprise Surveys, in 90 countries with procurement systems data from Public Expenditure and Financial Accountability (PEFA) assessments. We find that in countries with better public access to complete, reliable, and timely procurement information, firms are more likely to participate in public procurement markets. Firms report paying less in kickbacks to officials in countries where exceptions to open competition in tendering must be explicitly justified, and where there are effective and independent complaints mechanisms. These findings—particularly on kickbacks—are robust to the inclusion of numerous controls and to a range of sensitivity tests. However, due to data limitations we are unable to rule out the possibility that these estimates may reflect in part endogeneity bias.